GESAMSU (Gedrik Saruk Memang Seru) Based Environmental: Effectiveness Of Games On Mathematics Communication Ability Of Elementary School Students - Andayani Andayani; Alpin Herman Saputra; Eri Irianto; Bramianto Setiawan (STAI Hubbulwathan Duri, 2022)
This study aimed to determine the effectiveness of the GESAMSU (Gedrik Saruk Indeed Seru) game-based environment on students' mathematical communication skills. This research was conducted by 3rd-grade students at an Integrated Islamic Elementary School (IT) Nurul Islam Paramarta in Seputih Banyak District in Central Lampung, with a sample of 62 students in this study. This research method used Experiment with Control Group Design research type, using a random purposive sampling technique. The research design used in this study was the Pretest-Posttest Control Group Design. This study used an instrument in the form of an Essay test of mathematical communication skills. The results showed that the increase in students' mathematical communication skills who were taught by applying the Environmental-Based GESAMSU (Gedrik Saruk Indeed Seru) game was significantly higher than the increase in students' mathematical communication skills taught by conventional learning models. The average post-test score of the experimental class was higher than the post-test score of the control class, namely 85,96 and 60,63, both of which were in a different category.